Role of SAGA complex subunits in gene regulation of Candida albicans. Issue 12 (17th December 2021) - Rashid, Saima; Correia Mesquita, Tuana Oliveira; Whiteway, Malcolm
Abstract : The SAGA (Spt-Ada-Gcn5-acetyltransferase) is an evolutionary conserved multidomain co-activator complex involved in gene regulation through its histone acetyltransferase (HAT) and deubiquitinase (DUB) functions. It is well studied in Saccharomyces cerevisiae, and recent reports from humans and Drosophila expand its importance from gene transcription regulation to transcription elongation, protein stability and telomere maintenance. In Candida albicans, little is known about the components of the SAGA complex and their influence in morphogenesis and stress response. In this work, we analysed individual components of the SAGA complex, their role in morphogenesis and responses to different signalling cues. We initially analysed conditionally repressed strains of SAGA complex subunits involved in the HAT function of the complex: Tra1, Ngg1, Spt7, Spt8, Taf5, Taf6, Taf9, and Taf10. It appears that the Tra1 might be essential for the viability of C. albicans, as we failed to obtain homozygous deletions although it showed detectible growth in the conditionally repressed strain. Also, we observed that TBP- associated factors are essential in C. albicans, possibly due to their role in the transcription initiation factor TFIID instead of SAGA. We also detected that the Spt8 repressed mutant was extensively invasive in YPD at 300C while a repressed Ngg1 was considerably less invasive compared to its wild type. Also, we have seen that the mutations affecting TBP-binding ability confer susceptibility to drugs, temperature, osmotic, oxidative and DNA damage stress. Further, it seems that the modules of SAGA complex might have antagonistic roles in expression regulation but this needs more in-depth study.